Collective group learning - Ann K. Brooks (Adult Education Research Conference, 1993)
This qualitative case study of four teams sought to understand the process of collective group learning. The study resulted in identification of a general process of group learning. However, this process was found to be profoundly affected by national ideology as manifested in authority structures and policies within the teams' institutional environment.